Ineffective peripheral tissue perfusion in patients with diabetic foot: a mid-range theory - Lorrany Fontenele Moraes da Silva; Livia Maia Pascoal; Francisca Elisângela Teixeira Lima; Floriacy Stabnow Santos; Marcelino Santos Neto; Paula dos Santos Brito (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to develop a mid-range theory for nursing diagnosis ineffective peripheral tissue perfusion in patients with diabetic foot. Method: the theory construction was carried out in six stages: approach definition; theoretical-conceptual model definition; definition of the main concepts; pictogram development; construction of propositions and establishment of causal relationships evidence for practice. Results: twelve etiological factors and 22 clinical indicators were included in the theory, some of which were not listed in NANDA International (Inc.) and others were adapted to better characterize patients with diabetic foot. A pictogram was constructed and eight propositions were established to verify causal relationships and evidence for practice. Conclusion: medium-range theory made it possible to broaden the concepts and demonstrate the causal relationships between the elements of ineffective peripheral tissue perfusion, providing subsidies to minimize gaps in knowledge and assist clinical nursing practice.